2021
DOI: 10.1021/acsbiomaterials.1c00753
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Efficient Immunosensing Platform by Exploring Single-Walled Carbon Nanohorns (SWCNHs) and Nitrogen Doped Graphene Quantum Dot (N-GQD) Nanocomposite for Early Detection of Cancer Biomarker

Abstract: In this work, a novel electrochemical immunosensor based on nitrogen doped graphene quantum dot (N-GQD) and single-walled carbon nanohorns (SWCNHs) was developed for the detection of α-fetoprotein (AFP), a cancer biomarker. Thus, to fabricate the platform of the immunosensor, nanocomposite architecture was developed by decorating N-GQD on the surface of the SWCNHs. The resulting hybrid architecture (N-GQD@ SWCNHs) functioned as an exceptional base for the immobilization of antibody (Anti-AFP) through carbodiim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 43 publications
1
17
0
Order By: Relevance
“…Large surface areas of GQDs per unit mass with their edge functions make them suitable candidates for coupling with biological recognition elements and also for coating the working electrodes in electrochemical sensing applications. The scheme in Figure illustrates a simple GQD-based electrochemical sensor for detecting cancer biomarkers, α-fetoprotein (AFP) . The glassy carbon electrode (PG) was modified with N-GQD/SWCNHs, which are in turn coupled to AFP-specific antibody molecules via carbodiimide chemistry.…”
Section: Applications Of the Gqdsmentioning
confidence: 99%
“…Large surface areas of GQDs per unit mass with their edge functions make them suitable candidates for coupling with biological recognition elements and also for coating the working electrodes in electrochemical sensing applications. The scheme in Figure illustrates a simple GQD-based electrochemical sensor for detecting cancer biomarkers, α-fetoprotein (AFP) . The glassy carbon electrode (PG) was modified with N-GQD/SWCNHs, which are in turn coupled to AFP-specific antibody molecules via carbodiimide chemistry.…”
Section: Applications Of the Gqdsmentioning
confidence: 99%
“…FT-IR studies were performed for the catalyst (FNHDNi) and all of its fragmented parts, i.e., SWCNHs, FSWCNHs, and FSWCNHs@NiFe 2 O 4 @ L-dopa as well (Figure 5A−D). Pristine SWCNHs display bands at 1643 cm −1 for the skeleton vibration, 1172 cm −1 for the C−O stretching of saturated aliphatic ethers, 47 1554 cm −1 for the stretching of aromatic rings or C�C conjugated with C�O groups, and 2800−3000 cm −1 for sp 2 −C−H stretching. 48 Oxidized SWCNHs show quite a similar spectrum of p-SWCNHs, the only difference of having several new sharp bands centered at 1387, 1457, 1582, and 1733 cm −1 which appear due to the presence of the −COOH group.…”
Section: Synthesis and Characterization Of Ni(ii) Complexes 1− 2 (Nil)mentioning
confidence: 99%
“…Undoubtedly, graphene has received a lot of attention as a promising material for regenerative medicine and tissue engineering in various morphologies such as 2D nanosheets, , three-dimensional (3D) foams, nanofibers etc. , Of late, graphene and its derivatives are being investigated as biocompatible substrates for cell growth and proliferation. , Graphene-based substrates augment the adhesion, growth, proliferation, and differentiation of a variety of cells, including neural stem cells (NSCs), embryonic, pluripotent, and mesenchymal stem cells, in a majority of articles. , The major benefits of employing high-surface-area graphene-based nanomaterials (GMs) as suitable substrates include the ability to interface with the biological systems and transport a wide range of biomolecules, including DNA, enzymes, proteins, and peptides, via covalent bonds or non-covalent interactions such as π–π stacking in drug/gene delivery and biosensing applications. , The strong biocompatibility of GMs is another crucial feature that makes them a promising choice for biological applications. , GM is generally employed as a scaffold to establish a bridge between regenerated neurons due to its unique topographic and chemical features. , When supporting cells such as glial and neural precursor cells or stem cells are integrated into such a scaffold, the regeneration rate is increased. , Furthermore, investigations have shown that graphene’s high electrical conductivity can influence the motion of brain cells as well as its differentiation in the presence of an electric field . As a result, research suggests that GMs have tremendous potential as a biocompatible, carbon-based nanomaterials for nerve tissue engineering .…”
Section: Introductionmentioning
confidence: 99%
“…20,21 GM is generally employed as a scaffold to establish a bridge between regenerated neurons due to its unique topographic and chemical features. 22,23 When supporting cells such as glial and neural precursor cells or stem cells are integrated into such a scaffold, the regeneration rate is increased. 24,25 Furthermore, investigations have shown that graphene's high electrical conductivity can influence the motion of brain cells as well as its differentiation in the presence of an electric field.…”
Section: ■ Introductionmentioning
confidence: 99%